Utilização do ambiente urbano por psitacídeos (Aves, Psittacidae) no interior do estado de São Paulo - Silva, Ana Cecília Castro Rodrigues (Universidade Federal de São Carlos, 2025)
Urbanization significantly impacts biodiversity, influencing the distribution and behavior of species. In this context, psittacine birds are increasingly observed in urban environments, but their ecological interactions in these settings are still poorly understood. Therefore, we investigated the resource exploitation by psittacines in the urban matrix of Sorocaba, São Paulo, Brazil, across dry and wet seasons. We hypothesized that (1) seasonal variations would affect resource use and reproductive behaviors, (2) species abundance would not be random, and (3) landscape characteristics would affect species presence. Data were collected between 2023 and 2024 at 40 random points distributed across the urban grid (80 hours of sampling effort). We recorded 343 sightings and 969 individuals from five species, with the White-eyed Parakeet (Psittacara leucophthalmus) being the most abundant (n = 672), followed by the Plain Parakeet (Brotogeris tirica) (n = 179) and the Cobalt-rumped Parrotlet (Forpus xanthopterygius) (n = 99). Regarding data analysis, GLMM models revealed that the abundance of Psittacara leucophthalmus was positively associated with impervious surfaces (p < 0.05), while Forpus xanthopterygius occurred more frequently in areas with greater tree and understory vegetation cover (p < 0.05). Furthermore, the diet of psittacines included fruits from native and exotic species, with higher consumption in the dry season (n = 38). We recorded 20 plant species consumed by psittacines, with black mulberry (Morus nigra) (n = 9) being the most consumed species. Additionally, reproductive behaviors, such as nest searching on rooftops, were more frequent at the end of the dry season, possibly synchronized with fruit availability in the pre-wet season. Finally, the study highlights the differential use of urban resources by psittacines and emphasizes the importance of landscape in shaping urban biodiversity. We conclude that these findings contribute to the understanding of urban ecological dynamics and support conservation strategies for birds in anthropized environments.
Use of the urban environment by psittacines (Aves, Psittacidae) in the interior of the state of São Paulo
Keywords: Aves Urbanas; Ecologia Urbana; Urbanização; Urban Birds; Urban Ecology; Urbanization; CIENCIAS BIOLOGICAS::ECOLOGIA; 11. Cidades e Comunidades Sustentáveis